Detection and Quantification of the Harmful Dinoflagellate Margalefidinium polykrikoides (East Asian Ribotype) in the Coastal Waters of China - Jiarong Hu; Ruoyu Guo; Douding Lu; Xinfeng Dai; Yuanli Zhu; Bum Soo Park; Pengbin Wang (Toxins, 2022)
As a marine ichthyotoxic dinoflagellate, Margalefidinium polykrikoides, previously named Cochlodinium polykrikoides, have caused mass mortalities of fish worldwide during blooms. Rapid detection of target species is a prerequisite for the timely monitoring and early warning of harmful algal blooms (HABs). However, it is difficult to achieve rapid identification with traditional methods. The technology of using quantitative real-time PCR (qPCR) to detect and quantify microalgae is relatively mature. Based on the accuracy, rapidity, and sensitivity of qPCR technology, it can be used in the monitoring and development of early warning systems for HABs. From 2017 to 2020, samples were collected from 15 locations off the Chinese coast or from local sea areas. Based on the qPCR detection and analysis, the target species, M. polykrikoides (East Asian ribotype, EAr), was found in samples from Tianjin, Yangtze River estuary, and offshore Fujian (East China Sea). This is the first time that M. polykrikoides (EAr) was detected in the coastal waters of Tianjin. The results reveal a distributive pattern of M. polykrikoides (EAr) along Chinese coastal waters. It is helpful to predict the future diffusion trend of M. polykrikoides (EAr) in the China Sea and provides a practical case for the future construction of monitoring and warning systems for M. polykrikoides and HABs.